Strategi Guru Dalam Penanganan Perilaku Tantrum Pada Anak Dengan Hambatan Wicara (Speech Delay) - Melwani, Saskia Dara; Rahmah, Rahmah; Herlinda, Susi (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This research is motivated by the complexity of managing children with speech delay accompanied by tantrum behavior in the school environment. The study aims to describe the teacher's role in assisting children with speech delay who experience tantrums at TK ABA II Pekanbaru. A qualitative method with a case study approach was employed, focusing on a 6-year-old boy. Data collection techniques included participatory observation, in-depth interviews, and documentation. The results indicate that teachers play crucial roles as facilitators, mentors, role models, and motivators. Strategies for handling speech delay involve activity-based language stimulation such as reading books, singing, and role-playing. Meanwhile, tantrums are managed through a persuasive approach by maintaining calmness, providing time-out sessions, and engaging in therapeutic communication once the child's emotions stabilize. The study concludes that the synergy between psychological assistance and language stimulation is vital in determining the child's successful adaptation in school.